Prevalence of Toxoplasma gondii in Sheep and Goats in Three Counties of Gilan Province, North of Iran the More Humid Climate the Higher Prevalence - Yashar Havakhah; Ahmad Reza Esmaeili Rastaghi; Samira Amiri; Jalal Babaie; Zohreh Aghighi; Majid Golkar (Pasteur Institute of Iran, 2014)
Introduction: Toxoplasma gondii is one of the most important foodborne pathogens. Toxoplasmosis causes abortion and neonatal loss in livestock and imposes significant losses to farming industry. Prevalence of T. gondii in sheep and goats was investigated in three adjacent geographical areas within Gilan province in north of Iran. Methods: Serum samples were collected from 247 sheep and 155 goats in three counties Roudsar with humid subtropical climate and average annual precipitation (AAP) of 1400 mm, Masal with sub-humid climate and AAP of 700 mm, and Roudbar with cold semi-arid steppe climate and AAP of 400 mm. The samples were tested for Toxoplasma antibodies by using Sabin- Feldman Dye Test. Results: The overall prevalence in sheep was significantly higher than goats (P<0.001). Moreover, the prevalence in sheep was greatly increased with AAP (P<0.001) the prevalence in sheep was 62.2% in Roudsar, 39.3% in Masal and 15% in Roudbar. Conclusion: Sheep is the most common source of meat consumed in Iran, as well as many parts of the world, and presents the most danger in foodborne transmission of T. gondii to humans. Intensive farm management resulted in decreased prevalence of Toxoplasma in poultries and pigs while sheep are raised in small flocks in Iran, as many other developing countries, and extensively exposed to oocysts shed by cats. The information obtained here could have important implications for prevention of T. gondii infection in humans as well as reducing the rate of infection, and consequent abortion and neonatal loss in sheep and goats.